2012
DOI: 10.1371/journal.pone.0045577
|View full text |Cite
|
Sign up to set email alerts
|

let-7b and miR-126 Are Down-Regulated in Tumor Tissue and Correlate with Microvessel Density and Survival Outcomes in Non–Small–Cell Lung Cancer

Abstract: Angiogenesis is a critical event in the development, progression, and spread of various human cancers, including lung cancer. Molecular mechanisms that underlie the complex regulation of angiogenic processes are poorly understood. However, an increasing body of evidence indicates miRNAs as important regulators of tumor angiogenesis. Forceps biopsies were collected from tumor tissue, surrounding tissue, and non-tumor tissue from 50 NSCLC patients. Lung tissue samples from individuals with no clinical evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 41 publications
3
76
0
Order By: Relevance
“…Quantitative PCR was used to analyze the expression of selected miRNAs as previously described 45 . Isolated RNA was reverse transcribed using miRNA-specific RT primers (RNU6B, hsa-let-7a, hsa-miR-21, and hsa-miR-223) and a TaqManH MicroRNA Reverse Transcription Kit (Applied Biosystems, Foster City, California, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative PCR was used to analyze the expression of selected miRNAs as previously described 45 . Isolated RNA was reverse transcribed using miRNA-specific RT primers (RNU6B, hsa-let-7a, hsa-miR-21, and hsa-miR-223) and a TaqManH MicroRNA Reverse Transcription Kit (Applied Biosystems, Foster City, California, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, TGFBR2 was reported as a direct target of miR-17-5p (Dews et al 2010). So far, the expression pattern for miR-9-5p in lung tumor versus non-tumor samples has been inconsistently reported: up-regulation (Crawford et al 2009;Kang et al 2013;Xu et al 2014), downregulation (Yanaihara et al 2006), or insignificant change in expression (Jusufovic et al 2012). To the best of our knowledge, there is no report on miR-130b-3p expression in NSCLC.…”
Section: Systematic Filtering Of Critical Mirnas In Nsclcmentioning
confidence: 97%
“…Meng et al52 also found that miR‐126 promotes the proliferation and/or migration of EPCs and enhances angiogenesis, thereby promoting thrombus organization and recanalization in rat inferior vena cava thrombosis model. In contrast, the down‐regulation of miR‐126 enhances VEGFA activity in lung cancer, oral cancer and breast cancer,53, 54, 55, 56 and the restoration of miR‐126 decreases VEGF and tumour size in lung cancer 53, 57. In addition, miR‐126 inhibits gastric cancer angiogenesis by significantly reducing VEGFA expression and the activation of its downstream genes, Akt/protein kinase B, mTOR and Erk1/2 in the gastric cancer cell lines SGC‐7901, MKN‐28 and MKN‐45 27, 58.…”
Section: Mirnas That Target Genes Involved In Angiogenesismentioning
confidence: 99%